If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -5(2 + -2x) = -10 5x + (2 * -5 + -2x * -5) = -10 5x + (-10 + 10x) = -10 Reorder the terms: -10 + 5x + 10x = -10 Combine like terms: 5x + 10x = 15x -10 + 15x = -10 Add '10' to each side of the equation. -10 + 10 + 15x = -10 + 10 Combine like terms: -10 + 10 = 0 0 + 15x = -10 + 10 15x = -10 + 10 Combine like terms: -10 + 10 = 0 15x = 0 Solving 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '15'. x = 0 Simplifying x = 0
| x-5+4=9 | | 2-6x=10-2x | | 10x+24(x-3)=336 | | 25-15+14=x | | g(t)=36000-1500t | | x-.75x=190 | | 6[x-(9x-6)]=4-5x | | x-7x=18 | | 3x-12(3+x)-4x=-(-5-x)-(7-1) | | 2x+2=-4x-16 | | y+y+2=-16 | | 14=7x+5 | | n+3+5=-6 | | 180=37x-13 | | 7+2/3x=13 | | 4x+21x=-119 | | 63=n+28 | | 5x-2-3-x+2=9 | | x(x+9)=x^2+15x+12 | | 25-15+14= | | 6x-7=7+4x | | 9m^3-3m^2p^2-3mp+p^3= | | v-13=-7(4v+6) | | 5(r-1)=2(-3-4)-6 | | -7+8.5=14.2 | | 17x^2+576=x(x+118)-46x | | .5x-3=1.15x+4 | | 17x-9=15x+3 | | 6n-5+6=-23 | | -8x^6+1= | | 5-(t+6)=-1+2(t-3) | | 3s^2-8s-11=0 |